Affect Decreasing Lung Function in Laundry Installation Worker At Rumah Sakit Umum Pusat H. Adam Malik, Medan - Wina Elizabeth Octaria Saragih; Nuryunita Nainggolan; Amira Permatasari Tarigan (Jurnal Respirologi Indonesia, 2018)
Background: Data from International Labor Organization (ILO) at 2005 shows that there are 250 million case of diseases that related to occupation which can also cause 300.000 death in the world with annual incidence rate of work related lung disease around 1:1000 worker. Laundry worker was included as group that has risk of having occupational pneumoconiosis. Method: This is a descriptive study using total sampling with sample number 24 patient, this study was done in Laundry Installation of Rumah Sakit Umum Pusat Haji Adam Malik Medan on November 2016. Examination was done by using questionnaire, physical examination, daily PEF (before and after working) for 14 days, spirometry, total room dust, total room bacterial colonization. Factors (age, sex, working duration, smoking history, p.2,5 dust exposure, bacterial exposure, safety equipment usage, and nutritional status) that had potential of affecting the decreasing lung function was assessed. Result: From PEF examination, we found mean variability 3.1%. from all worker, there are 9 workers that had decreasing lung function ≥3, 1%. From examination result of 9 sample, decreasing lung function mostly caused by smoking (55%) and p.2,5 dust exposure (66%) Conclusion: Smoking and p.2,5 dust exposure is the most common factors that affected decreasing lung function in laundry worker. (J Respir Indo 2018; 38(2): 109-14)